BluPrint magazine and the development of architctural journalism in the Philippines (1999-2015) - Lanyi, Br. Bela (2016)
The main motivation of this research was the need to evaluate the achievements of University of San Carlos- School of Architecture, Fine Arts and Designs (USC-SAFAD) architecture magazine, Lantawan, first published in 2008 in Cebu City. For a comparative analysis, an overview of architecture magazines in the country had to be prepared. In line with this, the researcher's attention was directed to BluPrint, The strongst existing purely architectural magazine which successfully accompanied the 15 years of Philippine architecture. The research starts with the rationale and a description of the research method, followed by a short history of architctural journalism in the Philippines and, based on interviews, the content and layout of the magazine itself. The researcher analyzes the present working conditions at BluPrint editors, writers, and staff and written data from the magazine itself. The research demonstrates how in a special, journalistic way, BluPrint's developmental periods reflect not only on stages of the history of contemporary architecture in the Philippines, but also how the architect's social prestige grew. In conclusion, the study proves that BluPrint has found its place in the Philippine market, without ousting their initiatives of architectural communication.
Keywords: Architecture periodicals; Bluprint (Periodical)